Pelatihan Penggunaan Aplikasi Augmented Reality (AR) untuk Meningkatkan Literasi Digital Guru di SMP Negeri 3 BP Peliung - Arini Rosa Sinensis; Thoha Firdaus; M. Iqbal Mustofa; Intan Puspita; Adi Chandra (Universitas Indraprasta PGRI, 2022)
In 2019 SMP Negeri 3 BP Peliung received assistance in the amount of 63 Gadget Units (Tablets) of the Evercross brand from the government with the aim that teachers can use them in learning. However, it has not been used properly. This is because the internet network at the school is not supported and the teacher's digital literacy is very low. The solution to this problem is to increase the ability of teachers in digital literacy in the use of Gadgets (Tablets) for learning media both offline and online by implementing Augmented Reality (AR) to optimize Gadgets (tablets) as learning media in the form of training and mentoring activities. The result of this training activity is that there is an increase in the understanding of the importance of teacher ICT literacy and understanding of AR as an innovative learning medium by 95.6%. Increased Teacher Digital Literacy by 87% and teacher skills in using AR by 78.2%.